Author 
Message 
TAGS:

Hide Tags

Director
Joined: 04 Sep 2015
Posts: 642
Location: India
WE: Information Technology (Computer Software)

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 07:53
IMO E
1: let x=1,b=2 f(a+b)=(1+2)^2+1=10, f(a)+f(b)=(1+1)+( 4+1)=7 so this option is wrong
2:let a=0 and b=1 (5^2(1))/3 not eqaul to (5^2(0))/3 + (5^2(1))/3 wrong
3: let a=0 and b=1 (3(0)+2)+(3(1)+2)=7 and 3(1)+2=5 and so this option is also wrong
4:let a=1 and b=2 root(2(1))+root(2(2))=2+root(2) root(2)(3)=root(6)
so f(a+b) not equal to f(a)+(b) and this option is wrong for this reason.
5:let a=1 and b=2 (24)^(3)=24^1*24^2
Option E is the correct answer.



Intern
Joined: 18 Feb 2017
Posts: 14

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 08:08
IMO E.
f(a+b)=f(a)∗f(b). Let's consider a=2 and b=3 for all the options.
1. f(x)=x^2+1 f(2)= 5 and f(3) = 10. f(2+3)= 26 =/= 50. Incorrect option.
2. f(x)=5^(2x)/3 f(2)= 5^(4)/3 and f(3)= 5^(6x)/3. f(5) = 5^(10x)/3 =/= 5^(10x)/9. Incorrect option.
3. f(x)=3x+2 f(2)= 8, f(3)= 11, f(5)=17 =/= 88. Incorrect option.
4. f(x)=√2x f(2)= 2, f(3)= √6, f(5)= √10 =/= 2√6. Incorrect option.
5. f(x)=24^x. f(2) =24^2 , f(3)=24^3, f(5) = 24^5 ==24^5. Correct option. .



CEO
Joined: 03 Jun 2019
Posts: 3179
Location: India
GMAT 1: 690 Q50 V34
WE: Engineering (Transportation)

Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
Updated on: 08 Jul 2019, 08:21
Which of the following function follows the rule: f(a+b)=f(a)∗f(b) \(A. f(x)=x^2+1\) \(f(a+b)= (a+b)^2+1\) \(f(a)= a^2+1\) \(f(b)= b^2+1\) \(f(a).f(b)= (a^2+1)(b^2+1)\) f(a+b)<>f(a).f(b) B. f(x)=5^2x/3 f(a+b)= 5^2(a+b)/3 f(a)= 5^2a/3 f(b)=5^2b/3 f(a).f(b)= 5^2(a+b)/9 f(a+b)<>f(a).f(b) C. f(x)=3x+2 f(a+b)= 3(a+b)+2 = 3a+3b+2 f(a)= 3a+2 f(b)= 3b+2 f(a).f(b)= (3a+2)(3b+2) = 9ab+6b+6a+4 f(a+b)<>f(a).f(b) \(D. f(x)=\sqrt{2x}\) \(f(a+b)= \sqrt{2(a+b)}\) \(f(a)=\sqrt{2a}\) \(f(b)=\sqrt{2b}\) \(f(a).f(b)=2\sqrt{ab}\) f(a+b)<>f(a).f(b) E. f(x)=24^x f(a+b)=24^(a+b) f(a)=24^a f(b)=24^b f(a).f(b)=24^a.24^b = 24^(a+b) = f(a+b) IMO E
_________________
Kinshook Chaturvedi Email: kinshook.chaturvedi@gmail.com
Originally posted by Kinshook on 08 Jul 2019, 08:15.
Last edited by Kinshook on 08 Jul 2019, 08:21, edited 2 times in total.



Intern
Joined: 10 Aug 2016
Posts: 23
Location: India

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 09:53
Which of the following function follows the rule: f(a+b)=f(a)∗f(b)
A. f(x)=x^2+1 f(a+b) = (a+b)^2 + 1 f(a)*f(b) = (a^2 + 1)*(b^2 + 1) clearly not equal. incorrect.
B. f(x)=(5^2x)/3 f(a+b) = (5^2(a+b))/3 f(a)*f(b) = (5^2a)/3 * (5^2b)/3 = (5^2(a+b))/9 Not equal. Incorrect.
C. f(x)=3x+2 f(a+b) = 3a + 3b +2 f(a)*f(b) = (3a+2)*(3b+2) Not equal. Incorrect.
D. f(x)=sqrt(2x) f(a+b) = sqrt(2(a+b)) f(a)*f(b) = sqrt(2a)*sqrt(2b) = 2*sqrt(ab) Not equal. Incorrect
E. f(x)=24^x f(a+b) = 24^(a+b) f(a)*f(b) = (24^a)*(24^b) = 24^(a+b). Equal. Correct.
Correct Answer: E



Manager
Joined: 18 Jun 2013
Posts: 102
Location: India
Concentration: Technology, General Management
GPA: 3.2
WE: Information Technology (Consulting)

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 10:19
Which of the following function follows the rule: f(a+b)=f(a)∗f(b)?
Method 1: As per the rule that needs to be true, we can foresee that if the variable is in exponentials then a mere multiplication can simply lead to addition and the rule can hold true for the equation.
As per this, we see that the options 2 and 5 are the only ones where the variable is completely in the exponentials.
In option 2 the denominator will not allow the rule to hold true as in the RHS it will multiply. Hence option 2 is not correct.
In option 5, we have no other issues and the variable in the exponentials will simply add up on multiplication of the entities and hence the rule will always hold true.
Now, we can plug in some sample values and see if our analysis is correct and mark the correct answer which is option E.
Method 2: Putting values. This method is fool proof but may take you a couple of minutes to solve this question.
Option 1: f(x)=x^2+1
f(1 + 1) = f(1) = 1^2 + 1 = 5 f(1) = 1^2 + 1 = 2
If rule is true here then, f(1 + 1) = f(1) * f(1)
However, 5 <> 2
Hence, f(1 + 1) <> f(1) * f(1)
Option 1 is not correct.
Option 2: f(x) = (5^(2x))/3
f(1 + 1) = f(2) = (5^(2*2)) / 3 = (5^4) / 3 = 625/3 f(1) = (5^(2*1)) / 3 = 25/3
If rule is true here then, f(1 + 1) = f(1) * f(1)
625/3 = 25/3 * 25/3 > Rule holds here.
f(1 + 0) = f(1) = (5^(2*1)) / 3 = 25/3 f(1) = (5^(2*1)) / 3 = 25/3 f(0) = (5^(2*0)) / 3 = 1/3
However, 25/3 <> 25/3 * 1/3
Now, f(1 + 1) = f(1) * f(1); BUT, f(1 + 0) <> f(1) * f(0);
Hence, rule holds true sometimes but not always for this option.
Option 2 is not correct.
Option 3: f(x) = 3x + 2
f(1 + 1) = f(2) = 3*2 + 2 = 8 f(1) = 3*1 + 2 = 5
If rule is true here then, f(1 + 1) = f(1) * f(1)
However, 8 <> 5 * 5
Hence, f(1 + 1) <> f(1) * f(1)
Option 3 is not correct.
Option 4: f(x) = sqrt(2*x)
Consider, f(1 + 1) = f(2) = sqrt(2*2) = 2 f(1) = sqrt(2*1) = sqrt(2)
If rule is true here then, f(1 + 1) = f(1) * f(1)
And, 2 = sqrt(2) * sqrt(2)
Now consider, f(2 + 3) = f(5) = sqrt(2*5) = sqrt(10) f(2) = sqrt(2*2) = 2 f(3) = sqrt(2*3) = sqrt(6)
However, sqrt(10) <> 2 * sqrt(6)
Hence, f(1 + 1) <> f(1) * f(1)
Option 4 is not correct.
Option 5: f(x) = 24^x
Consider, f(1 + 1) = f(2) = 24^2 f(1) = 24^1
If rule is true here then, f(1 + 1) = f(1) * f(1)
And, 24^2 = 24^1 * 24^1
Consider, f(2 + 3) = f(5) = 24^5 f(2) = 24^2 f(3) = 24^3
If rule is true here then, f(1 + 1) = f(1) * f(1)
And, 24^5 = 24^2 * 24^3
Hence Option 5 or Option E is correct.



Director
Status: Manager
Joined: 27 Oct 2018
Posts: 801
Location: Egypt
Concentration: Strategy, International Business
GPA: 3.67
WE: Pharmaceuticals (Health Care)

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 11:16
for \(f(x)=x^2+1\): f(a+b) = \((a+b)^2 + 1 = a^2 + b^2 + 2ab + 1\) f(a)∗f(b) = \(a^2 + 1 + b^2 + 1 = a^2 + b^2 + 2\) > not equal for all values
for \(f(x)=\frac{5^{2x}}{3}\): f(a+b) = \(\frac{5^{2(a+b)}}{3} = \frac{5^{2a}5^{2b}}{3}\) f(a)∗f(b) = \(\frac{5^{2a}}{3}*\frac{5^{2b}}{3} = \frac{5^{2a}5^{2b}}{9}\)> not equal for all values
for \(f(x)=3x+2\): f(a+b) = \(3(a+b) + 2 = 3a + 3b + 2\) f(a)∗f(b) = \((3a+2)(3b+2) = 9ab + 6b + 6a + 4\) > not equal for all values
for f(x)= \(\sqrt{{2x}}\): f(a+b) = \(\sqrt{{2(a+b)}} = \sqrt{{2a+2b}}\) f(a)∗f(b) = \(\sqrt{{2a}}* \sqrt{{2b}} = \sqrt{{4ab}} = 2\sqrt{{ab}}\) > not equal for all values
for \(f(x)= 24^x\): f(a+b) = \(24^{a+b}\) f(a)∗f(b) = \(24^{a}*24^{b} = 24^{a+b}\) > equal
E



Manager
Joined: 31 Jul 2017
Posts: 192
Location: India
Concentration: General Management, Leadership
GPA: 3.4
WE: Information Technology (Computer Software)

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 11:20
Which of the following function follows the rule: f(a+b)=f(a)∗f(b)?
A. f(x)=\(x^2+1\)
B. f(x)=\(5^2^x * 3\)
C. f(x)=3x+2
D. f(x)=\(\sqrt{2x}\)
E. f(x)=\(24^x\)
A  f(a) = \(a^2 +1\) f(b) = \(b^2 +1\) f(a+b) = \((a+b)^2 +1\). f(a) * f(b) = \(a^2*b^2 +a^2+b^21\) Clearly f(a+b) is not equal to f(a)∗f(b).
B  f(a)=\(5^2^a * 3\) f(b)=\(5^2^b * 3\) f(a+b)=\(5^2^(a+b) * 3\). f(a) * f(b) = \(5^2^a+b * 9\) Clearly f(a+b) is not equal to f(a)∗f(b).
C  f(a)=\(3a+2\) f(b)=\(3b+2\) f(a+b)=\(3(a+b)+2\). f(a) * f(b) = \(9ab+6a+6b+4\) Clearly f(a+b) is not equal to f(a)∗f(b).
D  f(a)=\(\sqrt{2a}\) f(b)=\(\sqrt{2b}\) f(a+b)=\(\sqrt{2(a+b)}\) f(a)*f(b)=\(\sqrt{4ab}\) Clearly f(a+b) is not equal to f(a)∗f(b).
E  f(x)=\(24^x\)
f(a)=\(24^a\) f(b)=\(24^b\) f(a+b)=\(24^(a+b)\) f(a) * f(b)=\(24^(a+b)\). Clearly f(a+b) is equal to f(a)∗f(b)
Hence E



Manager
Joined: 28 May 2019
Posts: 73

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 14:27
Which of the following function follows the rule: f(a+b)=f(a)∗f(b)? We have to look for the option in which addition and multiplication might result in same value. If we look at the answer choices we can eliminate A, C and D easily. But to make sure we will put value of x and check.
A. f(x)=x^2+1 f(a+b)= (a+b)^2+1 f(a)*f(b) = (a^2 + 1)* (b^2+1) after solving we do not get similar values.B. f(x)=5^2x/3 f(a+b)=5^2(a+b)/3 f(a)*f(b)=5^2a/3* 5^2b/3 After solving this we get same numerator but different denominator.C. f(x)=3x+2 f(a+b)=3(a+b)+2 f(a)*f(b)=(3a+2)*(3b+2) after solving we do not get similar values.D. f(x)=sq root of 2x f(a+b)=sq root of 2(a+b) f(a)*f(b)=sq root of 2a * sq root of 2b after solving we do not get similar values.E. f(x)=24^x f(a+b)=24^(a+b) f(a)*f(b)=24^a* 24^b We get similar values on both sides. Correct.
_________________
Pick yourself up, dust yourself off, and start again.
Success is the sum of all small efforts.
MAKE IT HAPPEN



Director
Joined: 30 Sep 2017
Posts: 959
GMAT 1: 720 Q49 V40
GPA: 3.8

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
08 Jul 2019, 23:39
Which of the following function follows the rule: f(a+b)=f(a)∗f(b)?
Let us try a=1, b=3, a+b= 1+3 = 4
A. f(x)=x^2+1  f(a+b)=f(4)=17  f(a)=f(1)=2, f(b)=f(3)=10, then f(a)∗f(b)= f(1)∗f(3) = 20  the above function does NOT follow the rule: f(a+b)=f(a)∗f(b)
B. f(x)=5^(2x)/3  f(a+b)=f(4)=(5^8)/3  f(a)=f(1)=(5^2)/3, f(b)=f(3)=(5^6)/3, then f(a)∗f(b)= f(1)∗f(3) = (5^8)/9  The above function does NOT follow the rule: f(a+b)=f(a)∗f(b)
C. f(x)=3x+2  f(a+b)=f(4)=14  f(a)=f(1)=5, f(b)=f(3)=11, then f(a)∗f(b)= f(1)∗f(3) = 55  the above function does NOT follow the rule: f(a+b)=f(a)∗f(b)
D. f(x)=√(2x)  f(a+b)=f(4)=√8  f(a)=f(1)=√2, f(b)=f(3)=√6, then f(a)∗f(b)= f(1)∗f(3) = √12  the above function does NOT follow the rule: f(a+b)=f(a)∗f(b)
E. f(x)=24^x  f(a+b)=f(4)=24^4  f(a)=f(1)=24^1, f(b)=f(3)=24^3, then f(a)∗f(b)= f(1)∗f(3) = 24^4  the above function does follow the rule: f(a+b)=f(a)∗f(b)
ANSWER IS (E)



Intern
Joined: 24 Mar 2018
Posts: 17
Location: India
Concentration: Operations, Strategy
GMAT 1: 620 Q48 V28 GMAT 2: 680 Q49 V34 GMAT 3: 710 Q49 V38
WE: Project Management (Energy and Utilities)

Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
Show Tags
09 Jul 2019, 03:48
A. f(x)=\(x^2\)+1
f(a+b) = \(a^2\)+\(b^2\)+2ab+1 f(a).f(b) = \(a^2\)\(b^2\)+\(a^2\)+\(b^2\)+1
Not equal
B. f(x)=\(5^{2x}\)/3
f(a+b) = \(5^{2a+2b}\)/3 f(a).f(b) = \(5^{2a+2b}\)/9
Not equal
C. f(x)=3x+2
f(a+b) = 3a+3b+2 f(a).f(b) = (3a+2)(3b+2)
Not equal
D. \(f(x)=\sqrt{2x}\)
\(f(a+b) = \sqrt{2(a+b)}\) \(f(a).f(b) = 2\sqrt{ab}\)
Not equal
E. f(x)=\(24^x\)
f(a+b) = \(24^{a+b}\) f(a).f(b) = \(24^{a+b}\)
Equal
Hence, option E.




Re: Which of the following function follows the rule: f(a + b) = f(a)*f(b)
[#permalink]
09 Jul 2019, 03:48



Go to page
Previous
1 2
[ 30 posts ]

